PENDIDIKAN DAN PELATIHAN SEBAGAI SARANA PENINGKATAN KOMPETENSI GURU DI SMP NEGERI 02 LINGGANG BIGUNG - . Rusdin (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This article aim is to describe and analyze invrove teacher Competence Through Education and Training Apparatus . Research focus as: Education and training in Public Administration, Education and training in technical and managerial education and training field. Sources of data taken from the informant and key informants. As the informant was a civil servant, and as a key informant was Head of Department. Analysis of the data used in the study was developed as an interactive model. The object of the research findings Increased competence of personnel resources committed In Secondary Schools 02 Linggang Bigung West Kutai.Keyword : Competence Teacher, Education and Training